Understanding the Relationship between the Attitudes of Preservice Teachers towards Their Professions and Teacher Self-Efficacy Levels - Rabiaa Saad Mohamed Alnaas; Majidah Mohammed Mohammed; Ahmed Elmabruk Abdssalm; Ali Hassien Mohamed Milad (Surman Journal of Science and Technology, 2024)
A teacher is one of the most delicate professions in the world, where the candidates shall expect several challenges along their path. Therefore, teaching extends beyond delivering the knowledge to the students, to communication with the school, students and the parents, preparing and creating teaching strategies, as well as managing the classroom environment to suite the educational purpose of the place. Moreover, through the literature review performed in this research, attitudes towards the teaching profession, in addition to efficiency in performing the essential tasks of the teacher, such as; classroom management, student management and instructional strategies, are all critical talents that shall be looked at in a teacher. In this study, a questionnaire involving 182 preservice teachers in Turkey, collecting objective personal data and subjective attitude and efficiency data, was performed. The aim of this study is understanding the relationship between the attitudes of the preservice teachers towards their professions and teacher self-efficacy levels. The results of the study show that there are no significant difference in terms of the students’ gender and educational level in terms of attitude and efficiency in the teaching profession. However, significant correlations were found between the mother and father’s education and the daily internet usage, as well as between the attitude and the efficiency dimensions.